Superfast Set, Strong and Less Degradable Mineral Trioxide Aggregate Cement - Abdullah Alqedairi; Carlos A. Muñoz-Viveros; Eugene A. Pantera; Marc Campillo-Funollet; Hussam Alfawaz; Ensanya Ali Abou Neel; Tariq S. Abuhaimed (International Journal of Dentistry)
Purpose. Despite the good sealing ability and biocompatibility of mineral trioxide aggregate (MTA), its slow setting, high degradation, and weakness limit its use in surgical endodontics and high stress-bearing areas. This study aimed to develop two new liquids to control these drawbacks. They were prepared from calcium chloride, fumed silica, and hydroxyapatite or calcium phosphate and coded “H” and “P,” respectively. Methods. Portland cement, Grey ProRoot® MTA, and white ProRoot MTA were mixed with distilled water (control) or liquid “H” or “P.” The pH, setting time, degradation rate, leachant/precipitate’ composition, compressive strength, and morphology were assessed. Results. Both liquids maintained MTA’s high alkalinity and reduced the setting time by 1-2 orders of magnitude. Both liquids, H in particular, significantly reduced the degradation rate of Grey ProRoot and White ProRoot MTA®. Calcite has been identified as the main phase of the leachant or precipitate formed during the cement’s degradation. Calcium hydroxide or hydroxyapatite was also identified with Grey ProRoot MTA mixed with H liquid. These liquids also significantly increased the compressive strength with no statistical differences between them; this was associated with the production of dense, consolidated structures. Conclusions. The modified MTA could be used in surgical endodontics and high stress-bearing areas.